Evaluation of Nepali Aggregates for Alkali-silica Reactivity Using Accelerated Mortar Bar Test Method - Acharya, Pawan; Gautam, Bishnu Prasad (Far Western Review, 2023)
In many countries, large concrete structures needed to be replaced by new structures because treatment of Alkali Silica Reaction (ASR) was not feasible. Availability of amorphous or poorly crystalline silica is a necessary condition for ASR and it has been a common problem in several countries located in cold geographical regions. Some Nepali rocks also comprise amorphous silica as detected in Sanjen Hydropower Project (SHP) and Tanahu Hydropower Project (THP) during the examination of aggregate through various tests. ASR kinetics and the resulting expansion are observed to be enhanced with an increase in temperature and humidity. Accordingly, the risk of ASR is expected to be prominent in Nepal where temperature and humidity are relatively high. However, systematic research on ASR in Nepal is scarce and the possibility of ASR is little known. This paper determines the reactivity of potential aggregate sources considered for some large infrastructures in Nepal. Accelerated mortar bar test based on the guidelines of ASTM C1260 was performed on aggregate specimens collected from the Pokhara Regional International Airport Project (PRIAP), THP, and SHP. 14-day longitudinal expansion of the mortar bar prepared from the aggregated collected from PRIAP, THP, and SHP was 0.1%, 0.17%, and 0.06% respectively. The aggregate collected from THP is deleterious, whereas aggregate collected from PRIAP and SHP is non-reactive. This study demonstrates that Nepal may have many sources of aggregates that are reactive.